NK Cell Metabolism and TGFβ – Implications for Immunotherapy - Slattery, Karen; Gardiner, Clair M. (Frontiers in Immunology, 2019)
NK cells are innate lymphocytes which play an essential role in protection against cancer and viral infection. Their functions are dictated by many factors including the receptors they express, cytokines they respond to and changes in the external environment. These cell processes are regulated within NK cells at many levels including genetic, epigenetic and expression (RNA and protein) levels. The last decade has revealed cellular metabolism as another level of immune regulation. Specific immune cells adopt metabolic configurations that support their functions, and this is a dynamic process with cells undergoing metabolic reprogramming during the course of an immune response. Upon activation with pro-inflammatory cytokines, NK cells upregulate both glycolysis and oxphos metabolic pathways and this supports their anti-cancer functions. Perturbation of these pathways inhibits NK cell effector functions. Anti-inflammatory cytokines such as TGFβ can inhibit metabolic changes and reduce functional outputs. Although a lot remains to be learned, our knowledge of potential molecular mechanisms involved is growing quickly. This review will discuss our current knowledge on the role of TGFβ in regulating NK cell metabolism and will draw on a wider knowledge base regarding TGFβ regulation of cellular metabolic pathways, in order to highlight potential ways in which TGFβ might be targeted to contribute to the exciting progress that is being made in terms of adoptive NK cell therapies for cancer.